Impact of Antimicrobial Stewardship Program Guidance on the Management of Community-Acquired Pneumonia in Hospitalized Adults. (4th October 2017) - Walsh, Thomas; Moffa, Matthew; Bean, Holly; Watson, Courtney; Bremmer, Derek
Abstract: Background: Community-acquired pneumonia (CAP) is often treated with prolonged antibiotic therapy and unnecessary utilization of broad-spectrum antibiotics. An Antimicrobial Stewardship Program (ASP) bundled initiative, which included dissemination of a clinical decision algorithm, procalcitonin guidance, and prospective audit with feedback by the ASP team, was implemented. Methods: A retrospective, pre-intervention/post-intervention study was conducted to compare management for patients admitted with CAP before and after implementation of the ASP-bundled initiative. The pre-intervention period was March 1, 2014 through October 31, 2014, and the intervention period was September 1, 2015 through April 30, 2016. Results: A total of 39 and 61 patients were included in the pre-intervention and post-intervention cohorts, respectively. When compared with the pre-intervention group, mean duration of therapy decreased (9.0 vs. 5.6 days; P < 0.001). More patients received an appropriate duration of 7 days or less (38.5% vs. 80.3%; P < 0.001), while fewer received courses of more than 10 days (28.2% vs. 3.3%; P < 0.001). Fewer patients received intravenous vancomycin (28.2% vs. 4.9%; P = 0.002) and anti-pseudomonal β-lactams (25.6% vs. 6.6%; P = 0.02). Pneumonia-related 30-day re-admission rates (5.1% vs. 4.9%; P = 0.99) were unaffected. In the post-intervention group, patients with procalcitonin levels < 0.25µg/L received shorter duration of therapy compared with patients with levels > 0.25µg/L (4.5 vs. 6.9 days; P = 0.001). Conclusion: A syndrome-specific approach to antimicrobial stewardship practices, incorporating procalcitonin-guidance, led to shorter durations of therapy and decreased use of broad-spectrum antibiotics for the treatment of CAP without affecting hospital re-admissions. Disclosures: All authors: No reported disclosures.